Upaya Meningkatkan Hasil Belajar Siswa Tentang Shalat Jenazah Melalui Metode Demonstrasi pada Pembelajaran Pendidikan Agama Islam - Sarni Sarni; Juliati Juliati; Ermawita Ermawita (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine efforts to improve student learning outcomes about funeral prayers through demonstration methods in Islamic religious education learning. The subjects in this study were students who participated in teaching and learning activities in funeral prayers. The method used in this study was classroom action research. Data were collected using observation sheets and interviews. Data analysis was carried out using qualitative descriptive techniques. The results of the analysis in cycle I showed that as many as 85% of students got a complete score in the ability to understand the material about funeral prayers. While in cycle II as many as 99% of students got a complete score in the ability to demonstrate funeral prayers. The results of the study showed that the application of the demonstration method can increase student learning motivation in the material of funeral prayers. Therefore, it is recommended that the demonstration method be applied more in learning in schools so that it can increase student learning motivation and the overall quality of learning.